Immediate-early genes in the central nervous system - Tölle, Thomas R.; Schadrack, J.; Zieglgänsberger, Walter (Springer Berlin Heidelberg, 1995)
The various chapters of this book provide a comprehensive, up-to-date overview of current methodology in the research of immediate-early genes and include a wide range of neurobiological topics, such as regeneration, memory formation, epilepsia and nociception. The contributors to this book have been selected from among the leading experts in their field of research